The Attention As a Key Element to Improve Tactical Behavior Efficiency of Young Soccer Players - Cabral de Andrade, Marcelo Odilon; González-Víllora, Sixto; Casanova, Filipe; Teoldo, Israel (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
The aim of this study was to examine the associations between attention and tactical behavior efficiency of young soccer players with similar formal practice time and competitive level. The sample consisted of 80 young male soccer players from Brazilian clubs. The Vienna Test System was used to assess players’ attention. The System of Tactical Assessment in Soccer (FUT-SAT) was used to assess players’ tactical behavior efficiency. The Generalized Linear Models were used to verify the associations between attention and tactical behavior efficiency. The results showed that attention is positively associated with tactical behavior efficiency of young soccer players. Based on the results, high levels of attention will enable young soccer players with similar formal practice time and competitive level to display better responses regarding the tactical actions of the game.